Analisis Prosedur Pelaksanaan Pengadaan Langsung Barang dan Jasa di PT. PLN Nusantara Power Services - Sven Inggil Anugerah Kretarto; R. Yuniardi Rusdianto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research examines the procedures for direct procurement of goods and services at PT. PLN Nusantara Power Services. Using field research method with a qualitative approach, the research was conducted through a Regular Internship program at the Head Office of PLN Nusantara Power Services Sidoarjo. The research results show that the procurement business process involves several main divisions, particularly the Operation & Maintenance division as the user and the Supply Chain Management division as the executor. There are four main methods in procurement implementation, namely; Direct Procurement, Limited Tender, Open Tender, and Direct Appointment. Direct Procurement becomes the most efficient method for small-value and low-risk procurement. The research recommends implementing advanced technological systems to optimize the procurement process and expanding vendor networks to increase the effectiveness of the company's procurement of goods and services.